A new genus of Lachesillidae (Psocoptera) from the Peruvian Amazonia - Aldrete, Alfonso N. García (Zootaxa, 2012)
Mockford & Sullivan (1986), proposed a higher classification of the psocopteran family Lachesillidae, in which they established the subfamilies Lachesillinae and Eolachesillinae. In the latter subfamily they created two tribes, Eolachesillini and Graphocaeciliini, and dealt with the systematics of the latter. In the Graphocaeciliini they recognised eight genera, including six new genera, and 29 species in total. Subsequently, García Aldrete (2006) erected the genus Waoraniella from the Ecuadorian Amazonia, and established for it the tribe Waoraniellini, in the Eolachesillinae; García Aldrete & Mockford (2011 b) described a second species of that genus, from the Reserva Florestal Ducke, near Manaus, Brazil, and indicated that a third species is known to occur in the Peruvian Amazonia, near Iquitos; finally, García Aldrete & Mockford (2011 a) described the genus Amazolachesilla, in the Graphocaeciliini, from the Brazilian state of Amazonas.